Global analysis of metastatic breast cancer policy gaps and advocacy efforts across the patient journey. (October 2018) - Thrift-Perry, Maia; Cabanes, Anna; Cardoso, Fatima; Hunt, Katherine Moose; Cruz, Tauane Araújo; Faircloth, Kyra
Abstract: Metastatic breast cancer (mBC) is an area with high unmet need across the world. Despite significant progress to meet patient need, current breast cancer (BC) policies fail to recognize the unique challenges of patients who are further along the cancer patient journey. This analysis aims to understand BC/mBC policy development at a global level and identify opportunities for further development. A comprehensive analysis of National Cancer Control Plans (NCCPs) policies and programs was conducted across 16 countries, which represent a diverse range of healthcare systems, economies and geographic regions. Examples of promising practices, implemented or initiated by civil society, are provided to demonstrate successful methods to address the identified policy gaps. The analysis finds that disparities in BC policy development exist across and within countries. Progress in BC policy is fragmented and skewed towards the early part of the patient journey e.g. awareness and stakeholder education, with key gaps remaining in diagnosis and patient identification. In addition, access to innovative mBC treatments, ongoing support and palliative care remain a challenge, while care coordination is limited due to inefficient referrals. Although government and policymaker action is fundamental, collaboration between different stakeholders is imperative to address unmet needs of BC/mBC patients alike. Policy initiatives and promising practices that demonstrate successful multi-stakeholder engagement can be replicated or used to inform further advocacy and policy development with the aim to address patient unmet needs. Highlights: There are persistent gaps in the level of BC policy development, particularly to address the needs of mBC patients. Differences in policy development exist across countries of similar or different development levels. Advocacy efforts, led by civil society, can address policy gaps. Success depends on collaboration between stakeholders and sharing experiences across countries (successes and failures).